Giving me hope: women's reflections on a breastfeeding peer support service - Thomson, Gill (Matern Child Nutr, 2011)
Breastfeeding peer support has been identified as a key intervention to help improve breastfeeding and exclusive breastfeeding rates. The World Health Organization, and, in the UK, the National Institute for Health and Clinical Excellence, recommend the implementation of sustainable peer support programmes. As part of an evaluation into a comprehensive breastfeeding peer support service in north‐west England, in‐depth interviews were conducted with 47 women who had received a breastfeeding peer support service. In this paper, we have drawn upon the work of Morse and colleagues to interpret the data in relation to behavioural manifestations of hope, together with insights into the strategies used by the peer supporters to augment hopefulness for women's breastfeeding goals. These theoretical and practice‐based findings offer insights into how the breastfeeding peer supporters provided realistic assessments across varying situational contexts, formed strategies and plans to help women overcome any obstacles, made women aware of any negative outcomes, mobilised external and personal resources to facilitate goal attainment, provided evaluations and feedback on women's (and infants') progress, and through praise, reassurance and instilling calm, the peer supporters helped women to focus their energy to achieve their breastfeeding goals. Practice‐based implications are considered.